Pengaruh Motivasi Kerja Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai Pada Kantor DPRD Di Kota Tangerang Selatan - Firlya Nurfadila Hasna; Hafis Laksmana Nur Aldy (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract The purpose of this study is to determine the effect of work motivation and the non-physical work environment on employee performance at the Regional House of Representatives (DPRD) Office of South Tangerang City, both partially and simultaneously. This study uses a quantitative method with an associative approach to examine the influence or relationship between two or more variables. The sampling technique employed is saturated sampling, resulting in a total of 95 respondents as the research sample. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing.The results of the study indicate that work motivation has a significant effect on employee performance, with a coefficient of determination of 46.8% and hypothesis testing showing that the t-value is greater than the t-table value (9.038 > 1.985). The non-physical work environment also has a significant effect on employee performance, with a coefficient of determination of 45.6% and hypothesis testing showing that the t-value is greater than the t-table value (8.838 > 1.985).Simultaneously, work motivation and the non-physical work environment have a significant effect on employee performance, as indicated by the regression equation Y = 31.100 + 0.293X₁ + 0.247X₂. The coefficient of determination is 50.3%, while the remaining 49.7% is influenced by other factors. Hypothesis testing shows that the F-value is greater than the F-table value (46.512 > 2.703).